2021
DOI: 10.4103/jpbs.jpbs_273_21
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Assessment of Bone Losses in the Postoperative Phase of Single Implant Placed in Mandibular First Molar Regions

Abstract: Background and Aim: Bone loss surrounding dental implant is an unavoidable phenomenon that occasionally leads to implant failure. Implant-related bone loss exhibits different patterns and rate as per oral milieu and hygiene habits. This study was aimed to clinically assess the crestal bone losses in the postoperative phase of single implant placed in mandibular first molar regions. Materials and Methods: The present in vivo study was planned and complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…[20][21][22] Previous publications have shown that primary stability has a pivotal role in success of "IL protocol"; diminished initial stability being a key factor in early implant failure. In contrast, another publication revealed a high final success rate of implants loaded immediately subjected to low insertion torques i-e < 25 N-cm [23][24][25][26][27][28][29][30] Hence, ideal value of insertion torque dictating successful osseointegration still needs to be set by conducting further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Previous publications have shown that primary stability has a pivotal role in success of "IL protocol"; diminished initial stability being a key factor in early implant failure. In contrast, another publication revealed a high final success rate of implants loaded immediately subjected to low insertion torques i-e < 25 N-cm [23][24][25][26][27][28][29][30] Hence, ideal value of insertion torque dictating successful osseointegration still needs to be set by conducting further investigations.…”
Section: Discussionmentioning
confidence: 99%